'The stigma attached isn't true of real life': Challenging public perception of dementia through a participatory approach involving people with dementia (Innovative Practice). (February 2017) - Reynolds, Laura; Innes, Anthea; Poyner, Christopher; Hambidge, Sarah
This paper discusses the potential impact of viewing public performances of an orchestra comprising people with dementia, family members, student volunteers and professional symphony orchestra members in contributing to challenging negative perceptions of dementia. Negative perceptions of dementia abound despite recent policy attempts to challenge the stigma associated with the condition. This paper reports on the findings from the performance element of a music project for people with dementia, known as the BUDI Orchestra, designed to replicate the traditional rehearse and perform cycle of musicians. Data were collected via self-completion questionnaires from audience members ( N  = 109) at three public performances. The performances exceeded the expectations of the general public, and findings suggest a positive impact on perceptions of dementia, demonstrating the power and potential of participatory approaches showcasing the achievements of those living with dementia when attempting to raise awareness of dementia and challenge negative perceptions.